Analysis of the Content of the PAI Curriculum in Schools - Nazid Zaki Fuadi; Muhammad Zuhdi; Bobi Erno Rusadi (Penerbit Presisi Pustaka, 2026)
The Islamic Religious Education (PAI) curriculum plays a strategic role in shaping the character, morals, and personality of students who are faithful and devout. This article aims to analyze the content of the PAI curriculum in schools to determine its alignment with the goals of Islamic education and the demands of modern times. The analysis covers curriculum development principles, foundational elements of preparation, and the transformation of the PAI curriculum in Indonesia across different eras. The results show that the PAI curriculum has undergone significant development, from a simple post-independence curriculum to the